Results of treatment of patients with diaphyseal fractures of long bones of extremities (a retrospective analysis) - Pobel, Yevgeny (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article contains an analysis of the results of treatment of 780 patients with diaphyseal fractures of extremity bones from 2006 to 2010. A detailed study of the structure of diaphyseal fractures, a distribution of the patients by the type and mechanism of the injury according to AO/ASIF classification, by methods of their surgical treatment and by follow-up years are given. The causes, which led to unsatisfactory results of treatment in patients with diaphyseal fractures, were revealed.